2014
DOI: 10.1097/md.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Relapses in Patients With Giant Cell Arteritis

Abstract: Giant cell arteritis (GCA) is a relapsing disease. However, the nature, chronology, therapeutic impact, and clinical consequences of relapses have been scarcely addressed. We conducted the present study to investigate the prevalence, timing, and characteristics of relapses in patients with GCA and to analyze whether a relapsing course is associated with disease-related complications, increased glucocorticoid (GC) doses, and GC-related adverse effects. The study cohort included 106 patients, longitudinally foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
73
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 26 publications
(72 reference statements)
14
73
2
5
Order By: Relevance
“…In clinical trials, 12–22% subjects developed ischemic symptoms 9,13 while in a retrospective study, 13% (7 of 54 patients) experienced symptomatic vascular complications 7 . In a prospective cohort of 106 patients with biopsy-positive GCA, only 1 patient developed new visual changes while none developed manifestations of large-vessel involvement during relapses 9 . The observation in our study may have to do with the inclusion of patients with large-artery manifestations from GCA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In clinical trials, 12–22% subjects developed ischemic symptoms 9,13 while in a retrospective study, 13% (7 of 54 patients) experienced symptomatic vascular complications 7 . In a prospective cohort of 106 patients with biopsy-positive GCA, only 1 patient developed new visual changes while none developed manifestations of large-vessel involvement during relapses 9 . The observation in our study may have to do with the inclusion of patients with large-artery manifestations from GCA.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective studies, at least 1 disease relapse was reported in 28% to 62% of patients 2,3,5,7,8 . Of the 3 prospective observational studies to date evaluating relapses in GCA, relapses were reported in 36% (21 of 58), 60% (15 of 25), and 68% (68 of 106) of patients 4,6,9 . The current study includes a large prospective cohort of patients with GCA with standardized assessments at regular intervals including comprehensive information on symptoms at relapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite early treatment with high-dose glucocorticoids, 34-79% relapse. [31][32][33][34] We cannot predict which patients are likely to relapse; identification of relapse is complicated by presentation with non-specific symptoms coupled with normal laboratory tests in up to 20%. 32 It is possible that VEGF may be a useful marker for the identification of relapsing patients, and this should be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%